Ferroelectric to paraelectric phase transition of BaTiO3 - Chen, Gaofeng. (2011)
In this project, the transition between ferroelectric and paraelectric phases of BaTiO3 (BTO) was studied. A BTO single crystal was heated up and cooled down through the Curie temperature (Tc) in an Atomic Force Microscope equipped with a heating stage. The piezoresponse of the single crystal was also monitored by piezoresponse force microscopy (PFM) with images being scanned at different temperatures, ranging from room temperature to around 180℃. PFM Y image data was further analyzed using 2D autocorrelation method. Amplitude images pixel distribution at all temperatures are fit by Gaussian function. Data and analysis show that phase transition of BTO between ferroelectric and paraelectric is a gradual process. At the vicinity of Curie temperature, there are small domains presenting and enhanced piezoresponse when sample is heated, showing a peak on amplitude versus temperature plot. However, no enhanced piezoresponse were found for cooling process.